Analisis Pengaruh Tranparansi dan Akuntabilitas Laporan Keuangan terhadap Tingkat Kepercayaan Donatur: Studi Kasus Pada Yayasan Yarhima - Ardhiarisca, Oryza; Novita Sari, Linda (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to explain the influence of financial report transparency and accountability on the level of donor trust in the Yarhima Orphanage. This research method is quantitative research. The population of this study was 44 regular donors and 9 orphan guardian donors with a total of 53 donors and the sample in this study was 53 donors using a census sample. The data source in this research is primary data using a questionnaire with a Likert scale. The statistical tool used to test the hypothesis is regression with the help of the SPSS application. The results of the analysis show that the variables of transparency and accountability have a significant effect on the level of donor trust.